Spontaneous right whole-lung torsion secondary to bronchial carcinoma: a case report. Issue 1 (December 2016) - Chrysou, Konstantina; Gioutsos, Konstantinos; Filips, Alexandra; Schmid, Roger; Schmid, Ralph; Kocher, Gregor
Abstract Background Spontaneous whole lung torsion is an absolut rarity and most cases occur after previous surgery. Case presentation We present the case of a spontaneous whole-lung torsion in a 82-year old man. The patient was referred to our thoracic surgery department from the emergency department of a referring hospital with rapidly progressive dyspnea. CT-scan revealed a 180° degree counterclockwise torsion of the entire right lung with complete atelectasis and congestion of the upper lobe as well as pleural effusion. Thoracoscopy confirmed lung torsion and revealed hemorrhagic infarction of the upper lobe. Subsequently thoracotomy and upper lobectomy were performed. Most likely the lung torsion occurred due to a combination of pleural effusion and venous congestion with complete atelectasis of the upper lobe as a result of adenocarcinoma of the upper lobe. Conclusions To our knowledge this is the first reported case of a patient presenting with lung torsion as the first symptom of lung cancer. When lung torsion is suspected rapid diagnosis is crucial in order to prevent hemorrhagic lung infarction.